Strategi Manajemen Perubahan Model ADKAR dalam Persiapan Implementasi Kurikulum Sekolah Di UPTD SD Negeri 9 Gandapura - Zoelkhairy, Zoelkhairy; Munawar, Munawar; Abdurrahman, Abdurrahman (Jurnal Ragam Pengabdian, 2026)
This study examines the implementation of the ADKAR (Awareness, Desire, Knowledge, Ability, and Reinforcement) change management model in preparing curriculum implementation at UPTD SD Negeri 9 Gandapura. Using a qualitative descriptive approach, data were collected through observation, semi-structured interviews, and document analysis involving the principal, teachers, the school supervisor, and curriculum-related documents. Data were analyzed using the interactive model of data analysis, consisting of data reduction, data display, and conclusion drawing, with validity ensured through source and method triangulation. The findings show that ADKAR was applied effectively in all five dimensions. Awareness was built through socialization and coordination meetings; Desire emerged from teachers’ commitment and motivation; Knowledge was strengthened through professional development, KKG activities, and independent learning; Ability was shown in lesson planning and student-centered instruction; and Reinforcement was supported by supervision, mentoring, and collaborative practice. The study concludes that ADKAR is a practical framework for managing curriculum change in elementary schools. These results indicate that leadership support and teacher collaboration are essential for sustaining reform and improving instructional quality.